2019
DOI: 10.2478/jomb-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of fgf23 and balp with bone mineral density in hemodialysis patients

Abstract: Summary Background Chronic kidney disease (CKD) is associated with numerous complications such as bone mineral disorder. The aim of our study was to analyze the correlation of bone turnover markers with Bone Mineral Density (BMD) measurements in Tunisian end stage renal diseases (ESRD) patients. Methods This study included 100 ESRD Tunisian patients. Their estimated glomerular filtration rate (eGFR) was < 15 mL × min-1 × (1.73 m2)-1, which requires hemodialysis. Bone-specific alkaline phosphatase (BALP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…BALP is a glycoprotein synthesized by osteoblasts that hydrolyzes pyrophosphate to produce phosphate during bone mineralization and contributes to hydroxyapatite precipitation. If bone mineralization is disturbed, osteoblasts synthesize more BALP as a negative feedback response ( 30 ), which may explain the high preoperative serum ALP activities identified in patients at high risk of hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…BALP is a glycoprotein synthesized by osteoblasts that hydrolyzes pyrophosphate to produce phosphate during bone mineralization and contributes to hydroxyapatite precipitation. If bone mineralization is disturbed, osteoblasts synthesize more BALP as a negative feedback response ( 30 ), which may explain the high preoperative serum ALP activities identified in patients at high risk of hypocalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…CKD is an extremely complex disease with complications like renal failure and bone mineral disorder. It has been observed that elevated levels of FGF23 were correlated with bone mineral density in the lumbar spine site in CKD patients [ 154 ]. Thus, FGF23 can be used to predict bone loss at the lumbar spine site in the end stages of CKD [ 154 ].…”
Section: Physiology and Clinical Significance Of Endocrine Fgfsmentioning
confidence: 99%
“…It has been observed that elevated levels of FGF23 were correlated with bone mineral density in the lumbar spine site in CKD patients [ 154 ]. Thus, FGF23 can be used to predict bone loss at the lumbar spine site in the end stages of CKD [ 154 ]. On the other hand, a low level of FGF23 is reported in hyperphosphatemic tumoral calcinosis [ 155 ].…”
Section: Physiology and Clinical Significance Of Endocrine Fgfsmentioning
confidence: 99%
“…FGF23 is a 32-kDa glycoprotein secreted by osteocytes and functions in calcium and phosphorus metabolism disorders [11], bone loss [12], vascular calcification [13] and other CKD-MBD events in patients with ESRD. In previous studies, some scholars proposed that FGF23 could predict bone loss in patients with ESRD through its strong correlation with bone mineral density (BMD) in lumbar spine sites and femoral neck sites [14,15]. However, Wohlfahrt P and Isakova T et al drew contradictory conclusions that FGF23 had no correlations with BMD and bone mass corrected for other factors such as height, eGFR and PTH levels [16,17].…”
Section: Introductionmentioning
confidence: 99%